Pyrethroid resistance persists after ten years without usage against Aedes aegypti in governmental campaigns: Lessons from São Paulo State, Brazil. - Maria de Lourdes Macoris; Ademir Jesus Martins; Maria Teresa Macoris Andrighetti; José Bento Pereira Lima; Denise Valle (Public Library of Science (PLoS), 2018)
BACKGROUND:Aedes aegypti, vector of dengue, chikungunya and Zika viruses, is found at high densities in tropical urban areas. The dissemination of this vector is partially the consequence of failures in current vector control methods, still mainly relying upon insecticides. In the State of São Paulo (SP), Brazil, public health managers employed pyrethroids against Ae. aegypti adults from 1989 to 2000, when a robust insecticide resistance monitoring system detected resistance to pyrethroids in several Ae. aegypti populations. However, pyrethroids are also the preferred compounds engaged in household applications due to their rapid knockdown effect, lower toxicity to mammals and less irritating smell. METHODOLOGY/PRINCIPAL FINDINGS:We evaluated pyrethroid resistance in Ae. aegypti populations over the course of a decade, from 2004 to 2015, after interruption of pyrethroid public applications in SP. Qualitative bioassays with papers impregnated with a deltamethrin diagnostic dose (DD) performed with insects from seven SP municipalities and evaluated yearly from 2006 to 2014, detected resistance in most of the cases. Quantitative bioassays were also carried out with four populations in 2011, suggesting a positive correlation between resistance level and survivorship in the DD bioassays. Biochemical tests conducted with seven insect populations in 2006 and 2015, detected increasing metabolic alterations of all major classes of detoxifying enzymes, mostly of mixed function oxidases. Genotyping of the voltage-gated sodium channel (AaNaV, the pyrethroid target-site) with a TaqMan real time PCR based technique was performed from 2004 to 2014 in all seven localities. The two kdr mutations, Val1016Ile and Phe1534Cys, known to be spread throughout Brazil, were always present with a severe decrease of the susceptible allele over time. CONCLUSIONS/SIGNIFICANCE:These results are discussed in the context of public and domestic insecticide use, the necessity of implementation of a strong integrated vector control strategy and the conceptual misunderstanding between 'vector control' and 'chemical control of vectors'.